用于浮托安装水池模型试验的纵荡护舷模拟装置 (2024)
本发明提供一种用于浮托安装水池模型试验的纵荡护舷模拟装置，包括一滑轨组件、一定位装置、一位置调节装置和一弹性模拟装置；所述滑轨组件固定于一船体，所述定位装置可沿所述滑轨组件往复运动地架设于所述滑轨组件上；所述位置调节装置固定于所述船体并与所述定位装置传动连接；所述弹性模拟装置沿所述滑轨组件延伸方向固定于所述定位装置，所述弹性模拟装置包括一弹性组件和一橡胶垫，所述弹性组件沿所述滑轨组件延伸方向与所述定位装置固定连接，所述橡胶垫固定于所述弹性组件远离所述定位装置的一端。本发明的一种用于浮托安装水池模型试验的纵荡护舷模拟装置，可移动、弹性性能佳。 The invention provides a surging fender simulation device for an uplift mounted pond model test. The device comprises a sliding rail assembly, a positioning device, a position adjusting device and anelastic simulation device. The sliding rail assembly is fixed to a hull, and the positioning device can be erected on the sliding rail assembly by reciprocating along the sliding rail assembly. The position adjusting device is fixed to the hull and is in transmission connection with the positioning device. The elastic simulation device is fixed to the positioning device in the stretching directionof the sliding rail assembly, and comprises an elastic assembly and a rubber pad, the elastic assembly is fixedly connected with the positioning device